The Relationship between Macro Nutrient Intake and Ultra Processed Food Consumption Level With The Incidence of Overweight Status in Early Adolescents : Literature Review - Shenita Meyeira Olvan (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Adolescence is a critical period characterized by rapid increases in height and body weight, accompanied by higher nutritional requirements. These changes are influenced by various factors, including macronutrient intake and the high consumption of ultra-processed foods (UPFs). This study aims to analyze the relationship between macronutrient intake and ultra-processed food consumption with the risk of overweight status among adolescents.This study employed a literature review design, with articles retrieved from scientific databases including PubMed, ScienceDirect, and Scopus. A total of ten international journal articles published between 2015 and 2024 were included in this review.The findings consistently demonstrate that excessive consumption of ultra-processed foods among early adolescents is associated with decreased diet quality, increased total energy intake, and a higher risk of overweight and obesity. The analysis further indicates that high UPF consumption disrupts macronutrient balance and significantly contributes to the development of metabolic disorders, even before the clinical manifestation of obesity.Overall, this narrative review emphasizes that high intake of ultra-processed foods in early adolescence is strongly linked to increased energy consumption, poor dietary quality, and a greater risk of overweight and metabolic disturbances. Therefore, early intervention through comprehensive nutrition education, active family involvement, and supportive public health policies is essential to prevent long-term adverse health outcomes